Pengaruh Pengawasan terhadap Kinerja Pegawai pada Dinas Pertanian dan Ketahanan Pangan Kabupaten Pandeglang - Viyulia Viyulia; Arenawati Arenawati; Agus Sjafari (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
The purpose research is to find out how the supervision of the agriculture and food security service in Pandglang Regency and the effectiveness of the performance of its employees, and to find out how much influence the supervision has on the effectiveness of the performance of its employees. This study uses an associative method with a quantitative approach. The population in this study were all civil servants and non-PNS employees. The sample in the study, namely the entire population that was used as the research sample, totaled 46 employees, taking the sample with total sampling. The entire population is used as a sample if it is below 100. Data collection techniques in this study are observation, direct observation at the research location, questionnaires, and library research. The results of this study, there is a positive and significant influence of the monitoring variable on the effectiveness of employee performance at the agriculture and food security service in Pandeglang district with the results of hypothesis testing if tcount > ttable then the hypothesis is accepted. From the results of the research with the help of SPSS v.23, the results were 5.960 > 2.015 with a significance level of 0.000 (0.000 <0.05). Meanwhile, in the interpretation table of the correlation coefficient, the correlation value is 0.612. This figure is in the range between 0.60-0.799 so that it has a strong level of influence. This means that if the value of the monitoring variable increases, the effectiveness of employee performance will also increase.